Biofuels from Pyrolysis of Third-Generation Biomass from Household and Garden Waste Composting Bin: Kinetics Analysis - Bruna Rijo; Ana Paula Soares Dias; Novi Dwi Saksiwi; Manuel Francisco Costa Pereira; Rodica Zăvoianu; Octavian Dumitru Pavel; Olga Ferreira; Rui Galhano dos Santos (Reactions, 2023)
The modern society produces large amounts of household waste with high organic matter content. The vermicomposting of household waste produces high-value humic substances and is a way to stabilize organic material for later use as raw material (3rd generation biomass) for bioenergy proposes. A 6-month matured compost, combining vegetable and fruit scraps from domestic trash and grass and shrub clippings from yard waste, was evaluated to assess its potential as a raw material in pyrolysis processes. The pyrolysis activation energy (Kissinger) of the composted material showed values in the range of 200–300 kJ/mol, thus confirming its suitability for pyrolysis processes with promising H2 yields. The treatment of the composted material with H2SO4 and NaOH solution (boiling; 1 mol/L) led to the production of solid residues that present higher pyrolysis activation energies, reaching 550 kJ/mol for the most resilient fraction, which makes them suitable to produce carbonaceous materials (biochar) that will have incorporated the inorganics existing in the original compost (ashes 37.6%). The high content of inorganics would play a chief role during pyrolysis since they act as gasification promoters.